Application of Combined Manure and Potassium Sulfate on The Vegetative Growth of Rose Apple (Syzygium aqueum) - Musyafaali, Musyafaali (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Rose apple is one of the horticultural commodities favored by the Indonesian people. Cultivation using planter bags is popular due to several advantages, such as faster fruiting and shorter plants, making them easier to harvest. Proper care, especially in the use of organic and inorganic fertilizers, greatly influences the results expected by farmers. This study aims to determine the effect of the combination of manure and potassium sulfate on plant height, stem diameter, number of new leaf shoots, and leaf greenness. The research was conducted using quantitative methods with observations every 14 days. The results showed that the combination of fertilizers affected the number of new leaf shoots on rose apple plants (Syzygium aqueum). The best treatment was KH6 (100 grams of potassium sulfate, 200 grams of goat manure, and 200 grams of cow manure), but it was not significantly different from KH2 (150 grams of potassium sulfate, 250 grams of goat manure, and 250 grams of cow manure) and KH8 (150 grams of potassium sulfate, 150 grams of goat manure, and 150 grams of cow manure). The combination of fertilizers also affected leaf greenness at 14 DAT but did not affect it at 28 DAT and 42 DAT. The H2 treatment (200 grams of goat manure and 200 grams of cow manure) produced the greenest leaves compared to all other treatments but was not significantly different from KH3 (100 grams of potassium sulfate, 250 grams of goat manure, and 250 grams of cow manure).